Use of topical steroids in dermatology: A questionnaire based study - Sonali R Karekar; Padmaja A Marathe; Vetrivel Babu Nagarajan; Uday S Khopkar; Siddhi B Chikhalkar; Priyashree K Desai; Minakshi S Dongre (Wolters Kluwer Medknow Publications, 2020)
Context: Topical steroids, the most widely prescribed drugs in dermatology are being increasingly misused. Aims: This study was conducted to assess knowledge and practices regarding the use of topical steroids and to analyze prescriptions containing topical steroids. Subjects and Methods: Following approval from the institutional ethics committee, participants were recruited as per the selection criteria and divided into those treated in the institution and those having outside prescription. They were administered a pre-validated questionnaire to assess knowledge and practices regarding the use of topical steroids. Statistical Analysis Used: Comparison of awareness between two patient categories was done using Chi-square test. Prescription variables were analyzed using descriptive statistics. Significance of P value was set at 0.05. Results: Out of 400 patients, 167 had external prescriptions whereas 233 were institutional patients. Only 5.5% of all patients knew about the type of drug prescribed whereas 31.25% were aware of the indication. A total of 33.75% of the patients knew topical steroids required a prescription and 5.6% said they were aware that topical steroid use was associated with side effects. Side effects were reported by 96 patients. Awareness regarding knowledge, indication, and need for prescription were significantly better in institutional patients whereas knowledge about side effects was lacking in both groups. Psoriasis was the most common indication overall whereas tinea was the most common indication (51.5%) among externally prescribed. Conclusions: Although this study showed that institutional patients had comparatively better knowledge than community-treated patients, there is a need to create more awareness among patients overall and implement measures to stop irrational prescribing practices in the community.